Possibilities of combined (KTP 532 nm and Nd: YAG 1064 nm) laser radiation in complex acne therapy - M. M. Tlish; M. I. Sashko; M. E. Shavilova; F. A. Psavok (Лечащий Врач)
Currently, the possibilities of laser radiation in the treatment of patients with acne are being actively investigated. In this regard, it is of interest to combine phototherapy based on a combination of direct bactericidal, anti-inflammatory, immunomodulatory and sebostatic action of a neodymium yttrium-aluminum garnet (Nd: YAG) laser and simultaneous elimination of local post-inflammatory vascular and pigmentary disorders using a potassium-titanyl phosphate laser (KTP). Objective was to study the clinical efficacy and tolerability of combined phototherapy with KTP and Nd: YAG lasers in the complex treatment of patients with moderate acne. 60 patients with acne of moderate severity with localization of rashes on the face were under observation, which, depending on the therapy, were divided into the main and comparison group of 30 people. All patients received topical benzoyl peroxide and clindamycin phosphate gel. In the main group, combined phototherapy with KTP and Nd: YAG lasers was additionally performed. Treatment efficacy was monitored dynamically by calculating the dermatological acne index, evaluating the processes of lipid peroxidation and local blood flow. The tolerability of therapy was studied by monitoring adverse reactions and the dermatological index of quality of life. Clinically, in the patients of the main group, by the end of the observation, a pronounced regression of inflammatory elements was recorded, characterized by significantly lower RIA values than in the comparison group. Also, in this group, a faster recovery of processes of lipid peroxidation and local microcirculation was noted, the studied parameters of which already on the 8th day of therapy significantly exceeded the values of the patients in the comparison group, and by the 12th day they did not differ from the parameters of healthy individuals. In the course of treatment, there were no pronounced local adverse reactions in any of the studied groups. By the end of the observation, the number of patients in the main group who believed that acne has an insignificant effect on their quality of life exceeded this indicator in the comparison group by 2.1 times. The inclusion of combined phototherapy with KTP and Nd: YAG lasers in the complex treatment of patients with moderate acne is accompanied by a pronounced positive dynamics of the skin pathological process, restoration of processes of lipid peroxidation mechanisms and local microcirculation, and is also well tolerated by patients.